Network Analysis of Research Collaboration in the Study of Social Conflict and Peace in Society - Wulandari, Wulandari; Judijanto, Loso; Pardede, Mahadi (West Science Social and Humanities Studies, 2024)
Research collaboration in the study of social conflict and peace is essential for advancing knowledge and addressing societal challenges. This paper employs a bibliometric approach to analyze the network of research collaboration in this field, focusing on interdisciplinary perspectives and evolving trends over time. Through network analysis, thematic clusters are identified, including conflict emergence, societal development, global issues, post-conflict justice, and peacebuilding efforts. The temporal component highlights shift in research focus from 2008 to 2014, indicating emerging trends such as peace education and societal belief. Furthermore, the heatmap overlay identifies potential future research topics, with less-explored areas offering opportunities for new contributions. This study provides valuable insights for researchers, policymakers, and practitioners involved in conflict resolution, peacebuilding, and social cohesion initiatives.